2019
DOI: 10.1038/s41467-019-12785-3
|View full text |Cite
|
Sign up to set email alerts
|

A mutualistic interaction between Streptomyces bacteria, strawberry plants and pollinating bees

Abstract: Microbes can establish mutualistic interactions with plants and insects. Here we track the movement of an endophytic strain of Streptomyces bacteria throughout a managed strawberry ecosystem. We show that a Streptomyces isolate found in the rhizosphere and on flowers protects both the plant and pollinating honeybees from pathogens (phytopathogenic fungus Botrytis cinerea and pathogenic bacteria, respectively). The pollinators can transfer the Streptomyces bacteria among flowers and plants, and Streptomyces can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 42 publications
7
91
0
Order By: Relevance
“…Streptomyces species are effective at colonizing the rhizosphere and endosphere of plant roots where they can promote plant growth and provide protection against disease (11)(12)(13)34,35). It has even been suggested that their diverse specialized metabolism and filamentous growth may have evolved to give them a competitive advantage in this niche since it occurred ~50 million years after plants first colonized land (3).…”
Section: Discussion Although Typically Described As Free-living Soilmentioning
confidence: 99%
“…Streptomyces species are effective at colonizing the rhizosphere and endosphere of plant roots where they can promote plant growth and provide protection against disease (11)(12)(13)34,35). It has even been suggested that their diverse specialized metabolism and filamentous growth may have evolved to give them a competitive advantage in this niche since it occurred ~50 million years after plants first colonized land (3).…”
Section: Discussion Although Typically Described As Free-living Soilmentioning
confidence: 99%
“…In addition to Lactobacillus, the core bacterial community of Source K included Bifidobacterium, which is speculated to be involved with pollen digestion in honey bees [22]. One library within Source K included a high abundance of Streptomyces, which has been previously detected in pollen stores of honey bees [76] and stingless bees [96], and is known to defend against pathogens including Paenibacillus larvae and Melisococcus plutonius that cause American foulbrood and European foulbrood disease, respectively [97,98]. The bacterial community of Source B was significantly more diverse compared to Source K, and contained higher abundances of Betaproteobacteria, Gammaproteobacteria, and Bacteroides within the Flavobacteriaceae and Sphingobacteriaceae family, which have been previously detected in beebread [43,88].…”
Section: Bacterial Communitymentioning
confidence: 99%
“…The microbial community in strawberry owers shifts throughout the growing season from one of high diversity (weeks 0-12) to one of low diversity (weeks 14-24), a pattern coincident with the loss of S. globisporus SP6C4, which we consider to be a core member of the ower microbial community [6]. Here, we recalculated strawberry ower microbial population data to identify the top 10 OTUs and the diversity of the microbial community throughout the growing season ( Fig.…”
Section: Microbiome Collapse and Diseasementioning
confidence: 99%
“…We previously observed collapse of the anthosphere microbial community structure coincident with the aging of strawberry plants [6]. In particular, the loss of diversity and reduction in population density of Streptomyces globisporus SP6C4, a core microbe, was negatively correlated with onset of two major anthosphere diseases, gray mold (Botrytis cinerea) which includes brown spots on ower petals, and blossom blight (Cladosporioides sp.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation